Cognitive analysis as a way to understand students' problem-solving process / Ting Su Ung … [et.al.]. - Ting, Su Ung; Ngee Kiong, Paul Lau; Abdul Manaf, Badron (2016)
Education in Malaysia is always examination-inclined and mathematics education is still predominately a process of knowledge transmission. Teaching essentially remains a process for passing on knowledge, during which educators present and explain concepts to students who listen, take notes, possibly ask questions, and solve problems. Learning is by memorization and reproducing mechanically the learned facts to solve problems. Malaysian students took part in the Trends in International Mathematics and Science Study (TIMSS) for the years 1999, 2003, 2007 and 2011. Since the average mathematics scale scores dropped from 519 to 508 to 474 and 440, the performance of mathematics by secondary school students has declined.